Accidental clozapine intoxication in a toddler: clinical and pharmacokinetic lessons learnt. (20th November 2012) - Toepfner, N.; Wohlfarth, A.; Naue, J.; Auwärter, V.; Berner, R.; Hermanns‐Clausen, M.
Summary What is known and Objective: Clozapine, a second generation antipsychotic which is relatively safe in overdose, has been used as an effective treatment alternative to traditional antipsychotics. The therapeutic use in children remains controversial. However, in accordance with the increasing prescription in adults, the accidental ingestion in childhood becomes more frequent. We report the youngest case of accidental clozapine ingestion. Case summary: A 13‐month‐old girl presented with acute respiratory insufficiency and coma of unknown origin. The medical history, laboratory and radiological assessment did not link to aetiology until an almost spontaneous arousal after 22 h pointed towards intoxication. The initial standard drug screening using immunoassay had been negative. Hence, liquid chromatography mass spectrometry/mass spectrometry (LC‐MS/MS) was performed, and clozapine was detected with a serum concentration of 736 ng/mL. What is new and Conclusion: This case illustrates the diagnostic and forensic pitfalls in a coma of unknown origin due to the limits of toxicological screening immunoassays. LC‐MS/MS analysis by an established method showed clozapine metabolites (norclozapine and clozapine‐N‐oxide) are detectable for longer period, especially in urine, when compared with clozapine. The clinical course is presented in unique correlation with plasma and urine concentrations of clozapine and its metabolites. The elimination pattern of clozapine in toddlers is similar to adults, and the toxic dose was found to be lower when compared with school‐age children and adults.